Hesperidin protects against diethylnitrosamine/carbon tetrachloride-induced renal repercussions via up-regulation of Nrf2/HO-1 signaling and attenuation of oxidative stress - Magdy S. Aly, Sanaa R. Galaly, Nadia Moustafa, Hanaa M. Mohammed, Sally M. Khadrawy, Ayman M. Mahmoud (Journal of Applied Pharmaceutical Science, 2017)
The kidney plays a central role in detoxification and excretion of toxic metabolites, and therefore is susceptible to toxicity by xenobiotics. Hesperidin is a citrus flavonoid with multiple beneficial therapeutic effects. Here, we investigated the possible modulatory effect of hesperidin on diethylnitrosamine (DEN)/carbon tetrachloride (CCl4)-induced nephrotoxicity in rats, pointing to the role of Nrf2/HO-1 signaling. Male Wistar rats received a single intraperitoneal injection of DEN. Two-weeks later, the DEN-induced rats received a subcutaneous injection of 3 ml/kg CCl4 once/week for 16 weeks. DEN/CCl4-induced rats were treated with 50 and 100 mg/kg hesperidin throughout the experiment. After 18 weeks, DEN/CCl4-induced rats showed renal injury evidenced by the significant increase in circulating kidney function markers as well as histopathological alterations. Concurrent supplementation of hesperidin significantly ameliorated kidney function markers and prevented renal tissue damage induced by DEN/CCl4. In addition, hesperidin treatment suppressed collagen deposition, lipid peroxidation and nitric oxide, and enhanced the antioxidant defenses in the kidney of DEN/CCl4-induced rats. Hesperidin up-regulated the expression of Nrf2 and HO-1 in the kidney of DEN/CCl4-induced rats. In conclusion, hesperidin prevents DEN/CCl4-induced nephrotoxicity via attenuation of oxidative stress and alleviation of the antioxidant defense system. These effects are mediated via up-regulation of Nrf2/ARE/HO-1 signaling pathway.
Keywords: Hesperidin, Diethylnitrosamine, Fibrosis, Oxidative stress, Nephrotoxicity.